Fundamentals of Cosmic Particle Physics - Khlopov, Maxim (New Delhi: Viva Books, 2013)
This current English translation of Prof. Khlopov$1 (Bs book "Osnovy kosmomikrofiziki", URSS, 2004 reflects the large number of scientific advances, both theoretical and experimental, within the discipline of cosmic particle physics in the last 10 years. Some of the topics that have been added or updated include HND or CMD+HND scenarios being implemented into sterile neutrino scenarios, the ramifications of extending the forms of dark matter with respect to our view of neutrinos, the origin of baryon matter and the need for nonbaryonic matter in current theories, problems the existence of dark matter raises with respect to cosmic particle physics and the relationship with (meta) stable (super) weakly interacting particles predicted by the extension of the standard model, restrictions on baryon and lepton photons, as well as problems associated with expansion, among others. These and many other topics are readdressed in light of recent experimental and theoretical developments. Other areas that will be of interest to the reader include the puzzles presented by direct and indirect effects of dark matter (e.g., results of experiments such as DAMA/NaI, DAMA/LIBRA and PAMELA) and may lead to nontrivial new solutions for the problem of its nature, like the existence of new stable families of quarks and leptons and composite dark matter scenario.s
References 409-426p.; Index 427-431p.
Keywords: Mirror world; Non-equilibrium; Hidden parameters